2014
DOI: 10.1111/cas.12475
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 receptor EP4 as the common target on cancer cells and macrophages to abolish angiogenesis, lymphangiogenesis, metastasis, and stem‐like cell functions

Abstract: We previously established that COX-2 overexpression promotes breast cancer progression and metastasis. As long-term use of COX-2 inhibitors (COX-2i) can promote thrombo-embolic events, we tested an alternative target, prostaglandin E2 receptor EP4 subtype (EP4), downstream of COX-2. Here we used the highly metastatic syngeneic murine C3L5 breast cancer model to test the role of EP4-expressing macrophages in vascular endothelial growth factor (VEGF)-C/D production, angiogenesis, and lymphangiogenesis in situ, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
125
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(129 citation statements)
references
References 54 publications
4
125
0
Order By: Relevance
“…However, these studies also showed that prostaglandin E receptor, which is a downstream regulator of COX-2 enzyme, plays critical role in regulation of stemness of BC cells. 60,61 We found that ASA was unable to regulate COX-2 expression at the protein levels in Aspirin prevents breast cancer cell growth G Maity et al Figure S3). Therefore, from these collective studies, we neither strongly support the involvement of COX-2 signaling nor are able to exclude that the COX-2 protein might not play any role in the growth of BC cells or breast tumor-initiating cells or both.…”
Section: Discussionmentioning
confidence: 97%
“…However, these studies also showed that prostaglandin E receptor, which is a downstream regulator of COX-2 enzyme, plays critical role in regulation of stemness of BC cells. 60,61 We found that ASA was unable to regulate COX-2 expression at the protein levels in Aspirin prevents breast cancer cell growth G Maity et al Figure S3). Therefore, from these collective studies, we neither strongly support the involvement of COX-2 signaling nor are able to exclude that the COX-2 protein might not play any role in the growth of BC cells or breast tumor-initiating cells or both.…”
Section: Discussionmentioning
confidence: 97%
“…The role of EP4 in tumor progression has also been reported in colonic tumors (21). Although EP4 activity on breast cancer cells promoted SLC phenotype (19), VEGF-C and -D production by cancer cells as well as tumor-infiltrating macrophages in situ was also attributed to EP4, explaining strong antitumor, antimetastatic, and SLC-reductive effects of EP4 antagonists in a murine breast cancer model (19). Thus, contribution of EP4 in both tumor and host cell-mediated events make it a promising therapeutic target in breast cancer.…”
Section: Introductionmentioning
confidence: 88%
“…For testing the ability of single cells to form spheroids or tumorspheres (in vitro surrogate of SLC), cells (1 Â 10 4 cells/mL) were passed through 8-mm filter (Falcon; BD Biosciences) and a syringe fitted with a 27-gauge needle, and plated in 6-well ultralow attachment plates (Corning), as previously described (19,39). All tumorspheres were grown in HuMEC (GIBCO) media supplemented with EGF (20 ng/mL; Invitrogen), basic fibroblast growth factor (FGF; 20 ng/mL; Invitrogen), and B27 (1:50 dilution; Life Technologies), and allowed to grow for 7 to 10 days, or until the majority of spheroids reached a diameter of 60 mm (19,39).…”
Section: Tumorsphere Formation In Vitromentioning
confidence: 99%
See 2 more Smart Citations